Investigating and determining the risk factors of neonatal seizures in NICU patients in the South of Iran - Ali Khaje; Seyed Hosein Soleimanzadeh Mousavi; Maryam Golmohammadi; Zeinab Tavakolikia; Ghasem Miri-Aliabad; Reza Keeykha; Maryam Keykha; Afshin Fayyazi; Mohammadhosein Akhlaghpasand (Hygeia Press di Corridori Marinella, 2021)
Introduction: The incidence of neonatal seizures has been reported at 1.8 to 8.6 in 1,000 live births. It seems that the brain of premature children is more susceptible to seizures. The causes of neonatal seizures comprise a range of neurological disorders, including hypoxic-ischemic encephalopathy (HIE), central nervous system infection, intracranial hemorrhage, and structural disorder of the brain. Among all, the most common cause is HIE. Given the risks and consequences of neonatal seizures, this study aimed to investigate their risk factors. Methods: This is a descriptive cross-sectional study of 92 neonates, aged < 28 days, admitted to Neonatal Intensive Care Unit (NICU) during the period from March 2011 to May 2014, with the diagnosis of seizures. Demographic data including age, sex, gestational age, birth weight, fifth minute Apgar score were extracted from patient files. Data were analyzed using SPSS® version 19 software. Results: Of 92 cases, 12 (13.0%) had the fifth minute Apgar score above 8, 79 (85.9%) had Apgar score between 3 and 8, and 1 (1.1%) had Apgar score less than 3. Asphyxia was present in 63 (68.5%) infants. Seizure types were clonic in 41 (44.6%) cases, myoclonic in 20 (21.7%) cases, of mild type in 14 (15.2%) cases, and tonic in 17 (18.5%) cases. Metabolic disturbances revealed hypoglycemia in 7.6%, hypocalcemia in 2.2%, hyponatremia in 4.3%. Hereditary metabolic disorders were observed in 6.5% of patients. Conclusion: HIE was the most common cause of neonatal seizures, and cerebral hemorrhage and metabolic disorders were other two major causes of seizures after HIE. The most common type of seizures was the clonic type. The results suggest that male gender and a postnatal age < 2 weeks are associated with an increased risk of seizure in normal and premature infants.